Penerapan Model Pembelajaran Kooperatif Think Pair Share (Wordwall) Untuk Meningkatkan Pemahaman Siswa Pendidikan Agama Islam SMPN 1 Bantarujeg - Pipin Pirnawati; Nurhidayat Nurhidayat; Ahmad Zacky Burhani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the implementation of the Think Pair Share (TPS) cooperative learning model assisted by Wordwall in improving students’ understanding in Islamic Religious Education subjects at class VIII C of SMPN 1 Bantarujeg. This study used the Classroom Action Research (CAR) method based on the Stephen Kemmis and Robin McTaggart model, which consists of planning, action, observation, and reflection stages. The subjects of this study were 26 students. The research was conducted in two cycles, and the data were collected through observation, interviews, and learning outcome tests.The results showed that the implementation of the TPS learning model assisted by Wordwall was able to improve students’ understanding and activeness in the learning process. This can be seen from the increase in the average scores and the percentage of students’ learning mastery in each cycle. In the pre-cycle stage, the average score was 82 with a learning mastery percentage of 76.92%. In cycle I, the average score increased to 92 with a mastery percentage of 96.15%, and in cycle II, the average score increased to 96 with the mastery percentage remaining at 96.15%. In addition, students became more active in discussions, asking questions, and expressing opinions during the learning process. Therefore, the implementation of the Think Pair Share (TPS) cooperative learning model assisted by Wordwall was proven effective in improving students’ understanding in Islamic Religious Education subjects.